Penerapan Metode WASPAS Dalam Pemilihan Handphone Gaming Terbaik - Bahagia Elfrando Nababan; Theresya Yohana Jesica Nainggolan; Mesran Mesran (TIN: Terapan Informatika Nusantara, 2022)
Nowadays people cannot be separated from cellphones. Mobile phones are a communication and technology tool that is commonly used to make it easier for users to communicate and do various things, such as playing games. To be able to play games, you need very good cellphone specifications, for example battery life, high RAM, high screen resolution, and a good cellphone processor. So, a decision support system is needed in choosing the best cellphone for playing games so that it can help cellphone users in determining the best gaming cellphone. Therefore, in needing to choose the best gaming cellphone, we can use the WASPAS (Weighted Aggregated Sum Product Assessment) method to get a ranking of the best gaming cellphones.